Few-layer graphene sheets with embedded gold nanoparticles for electrochemical analysis of adenine - Biris AR (Dove Medical Press, 2013)
Alexandru R Biris,1 Stela Pruneanu,1 Florina Pogacean,1 Mihaela D Lazar,1 Gheorghe Borodi,1 Stefania Ardelean,1 Enkeleda Dervishi,2 Fumiya Watanabe,2 Alexandru S Biris2 1National Institute for Research and Development of Isotopic and Molecular Technologies, Cluj-Napoca, Romania; 2Center for Integrative Nanotechnology Sciences, University of Arkansas at Little Rock, Little Rock, AR, USA Abstract: This work describes the synthesis of few-layer graphene sheets embedded with various amounts of gold nanoparticles (Gr-Au-x) over an Aux/MgO catalytic system (where x = 1, 2, or 3 wt%). The sheet-like morphology of the Gr-Au-x nanostructures was confirmed by transmission electron microscopy and high resolution transmission electron microscopy, which also demonstrated that the number of layers within the sheets varied from two to seven. The sample with the highest percentage of gold nanoparticles embedded within the graphitic layers (Gr-Au-3) showed the highest degree of crystallinity. This distinct feature, along with the large number of edge-planes seen in high resolution transmission electron microscopic images, has a crucial effect on the electrocatalytic properties of this material. The reaction yields (40%–50%) and the final purity (96%–98%) of the Gr-Au-x composites were obtained by thermogravimetric analysis. The Gr-Au-x composites were used to modify platinum substrates and subsequently to detect adenine, one of the DNA bases. For the bare electrode, no oxidation signal was recorded. In contrast, all of the modified electrodes showed a strong electrocatalytic effect, and a clear peak for adenine oxidation was recorded at approximately +1.05 V. The highest increase in the electrochemical signal was obtained using a platinum/Gr-Au-3-modified electrode. In addition, this modified electrode had an exchange current density (I0, obtained from the Tafel plot) one order of magnitude higher than that of the bare platinum electrode, which also confirmed that the transfer of electrons took place more readily at the Gr-Au-3-modified electrode. Keywords: graphene, gold nanoparticles, chemical vapor deposition, oxidation of adenine